Influence of Hybridization on Mechanical Properties and Water Absorption in Jute and Jute /E-Glass Reinforced Composites - Lacerda, Vitor da S.; Conceição, Ana C. R. da; Scherer, Catarina da N.; Santos, Michel G.; Leão, Mirtânia A. (Journal of Research Updates in Polymer Science, 2021)
The use of composite materials is increasingly present not only in several industrial areas but also in daily life. With the escalating environmental concern, it is necessary the search for materials that prove to be ecologically sustainable and economically viable. Vegetable fibers have been presenting themselves as an excellent alternative, however, because their disadvantage of having a high moisture absorption capacity, the introduction of synthetic fibers, forming hybrid composites, is a good solution since it combines the characteristics of both types of reinforcements. The present research aims to carry out a comparative study between two types of laminated polymer composites, one reinforced with Jute fibers and the other hybrid, composed of Jute and E-glass fibers. The mechanical performances of the composites submitted to the Uniaxial Tensile, Three-point Flexural and Shear tests were evaluated, as well as fracture analyzes. A comparative study to analyze the influence of hybridization on moisture absorption was carried out. The results showed that the hybridized composite showed an increase in the elastic modulus, as well as in its resistance to flexion and shear, which shows the formation of a more rigid material. Hybridization also changed the moisture content of the composite.